Visual Learning in Application of Integration - Shafie, Afza; Janier, Josefina Barnachea; Wan Ahmad, Wan Fatimah (Springer Berlin / Heidelberg, 2010)
Innovative use of technology can improve the way how Mathematics should be taught. It can enhance student’s learning the concepts through visualization. Visualization in Mathematics refers to us of texts, pictures, graphs and animations to hold the attention of the learners in order to learn the concepts. This paper describes the use of a developed multimedia courseware as an effective tool for visual learning mathematics. The focus is on the application of integration which is a topic in Engineering Mathematics 2. The course is offered to the foundation students in the Universiti Teknologi of PETRONAS. Questionnaire has been distributed to get a feedback on the visual representation and students’ attitudes towards using visual representation as a learning tool. The questionnaire consists of 3 sections: Courseware Design (Part A), courseware usability (Part B) and attitudes towards using the courseware (Part C). The results showed that students demonstrated the use of visual representation has benefited them in learning the topic.